2006
DOI: 10.1002/jhbs.20169
|View full text |Cite
|
Sign up to set email alerts
|

The social control of behavior control: Behavior modification,individual rights, and research ethics in America, 1971–1979

Abstract: In 1971, the U.S. Senate Subcommittee on Constitutional Rights began a three-year study to investigate the federal funding of all research involving behavior modification. During this period, operant programs of behavior change, particularly those implemented in closed institutions, were subjected to specific scrutiny. In this article, I outline a number of scientific and social factors that led to this investigation and discuss the study itself. I show how behavioral scientists, both individually and through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
(20 reference statements)
0
13
0
1
Order By: Relevance
“…This argument extends from the work of scholars who have shown that, in the twentieth century, the thorniest moral questions in science are commonly recast as technical puzzles that experts can solve, even as that recasting is challenged (Evans, 2002;Rose, 2007;Rutherford, 2006). As I have shown, when ways-of-knowing combine with…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…This argument extends from the work of scholars who have shown that, in the twentieth century, the thorniest moral questions in science are commonly recast as technical puzzles that experts can solve, even as that recasting is challenged (Evans, 2002;Rose, 2007;Rutherford, 2006). As I have shown, when ways-of-knowing combine with…”
Section: Resultsmentioning
confidence: 66%
“…114-117;Robins, Gosling, & Craik, 1999). But, as Alexandra Rutherford (2006Rutherford ( , 2009 has argued, the remaining pockets of neobehaviorists were nonetheless ardent and vocal in their views.…”
Section: The Resilient Selfmentioning
confidence: 99%
“…This would change in the early 1970s, as research methods in behavioral modification fell under scrutiny. This criticism centered on the coercive aspect of subject participation, particularly in studies and interventions carried out on vulnerable populations, and in particular, prisoners (Rothman, ; Rutherford, ). Yet even so, this debate would not have been seen relevant at the time to Zubek's work, which focused in the 1970s on charting physiological variation in response to changes in environmental factors.…”
Section: Resultsmentioning
confidence: 99%
“…They argue that if prison is punishment, it is an ineffective punisher. Their paper provides a preliminary behavioral analysis of the problem and suggests that a solution must be a multidisciplinary effort, which may avoid some of the problems that arose in past behavioral applications in corrections (Rutherford, 2006). Their recommendations are very much in line with advances in behavioral systems analysis (Diener, McGee, & Miguel, 2009;Ludwig & Houmanfar, 2009;Malott, 2016;McGee & Diener, 2010;Reimer & Houmanfar, 2017;Sigurdsson & McGee, 2015), so perhaps this paper may occasion some synergy.…”
Section: Going Forwardmentioning
confidence: 94%